SURAU SEBAGAI BASIS ISLAMISASI KULTURAL MASYARAKAT MINANGKABAU - Welhendri Azwar (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Observing various dakwah activity today, rather feels that the essence of dakwah began to lose value. Dakwah is no longer able to give directions over the life of the Islamic community. Moreover, if the dakwah activity is packed with business media, especially television, this may seem to add “syi'ar”of Islam, but actually she's dragged to the artificiality meaning of divine messages. Dakwah activity tends to significantly spectacle, versus guidance. When studied in the early development of Islamic Dakwah, it’s succeeded in giving the color of people's lives. Dakwah instead act to strengthen the local culture with a strong Islamic characterize. Islam in Minangkabau characterize it has become increasingly apparent. The combination of local and Islamic culture are felt in many Minang people's lives. One of the most influential cultural symbol in Minangkabau is the message of Islam,